Wheat Markets and Price Stabilisation in Pakistan: An Analysis of Policy Options (The Pakistan Development Review, 2008)
This article provides a quantitative analysis of the effects of Pakistan government domestic wheat procurement, sales, and trade policies on wheat supply, demand, prices, and overall inflation. Analysis of price multipliers indicates that increases in wheat procurement prices (one means of promoting domestic procurement) have relatively small effects on the overall consumer price index. Partial equilibrium analysis of wheat markets suggests that fluctuations in production, rather than market manipulation, are plausible explanations for price increases in recent years. Comparisons of domestic and international prices suggest that promoting private sector imports is one alternative for increasing supply and stabilising market prices, particularly in years of production shortfalls. Overall, this paper concludes that market forces play a dominant role in price determination in Pakistan, and that policies that promote the private sector wheat trade can both increase price stability and reduce fiscal costs.